Performance analysis of Laravel and Yii2 frameworks based on the MVC architectural pattern and PHP language - Węgrzecki, Konrad Sławomir; Dzieńkowski, Mariusz (Journal of Computer Sciences Institute, 2022)
The subject of this paper is the performance analysis of two PHP programming frameworks in the latest versions - Laravel 9.6 and Yii 2.0.45. It was carried out with the help of test applications prepared for this purpose, which have identical functionalities: they generate all prime numbers from a given range and create a book ranking system based on CRUD operations. The request handling time of each application was used as a comparison criterion. To check the performance, dedicated debugbars - bottom bars displaying information about the executed request - were used. The results obtained after the tests showed that in terms of performance, Laravel is a better technology than Yii for building web applications.